The Role of Organizational Culture and Commitment towards Organizational Citizenship Behavior of Company Employees in Pasuruan, Indonesia - Ainun Zariyah; Dewi Komala Sari (Universitas Muhammadiyah Sidoarjo, 2019)
This study aims to determine the effect of organizational culture, work environment and organizational commitment to organizational citizenship behavior (OCB) Employees of the Production Section of PT.X Beji. This research is quantitative research with hypothesis testing. The sample used in this study was 73 production department employees at PT.X Beji. The analytical tool used in this research is multiple linear regression analysis using SPSS version 18 for windows. The primary data in this study were obtained from a questionnaire whose measurements used a Likert scale that was tested for validity and reliability. The results of this study prove that organizational culture influences organizational citizenship behavior (OCB), work environment influences organizational citizenship behavior (OCB), organizational commitment also influences organizational citizenship behavior (OCB), in addition organizational culture, work environment and organizational commitment influence simultaneously on organizational citizenship behavior (OCB).